3
$\begingroup$

So I have $\displaystyle{\,\mathrm{f}\left(\, x\, \right) = \frac{x - 1}{\,\sqrt{\, 3 - x\,}\,}}$

And I want to calculate $\,\mathrm{f}^{\mathrm{\left(\, 2015\, \right)}} \,\left(\, 1\,\right)$

So I got the first and second derivative: $$\mathrm{f}'(x)=\frac{-x+5}{2[(-x+3)^{\frac{3}{2}}]}$$ $$ \mathrm{f}''(x)= \frac{-2(-x+3)^{\frac{3}{2}} + (-x+5)\sqrt{-x+3}}{4(-x+3)^3}$$

Perhaps I should look at some of the next derivatives for pattern? or is that not going to help, there is also a formula I know for getting a high order derivative, but it's not going to help if I don't calculate all 2014 of them as well... So any help with this would be appreciated.

$\endgroup$
  • 1
    $\begingroup$ Ok usually you try to find some dependence of the number of derivatives and your derivative and guess an answer which you show then by induction; I try to be precisely in an answer $\endgroup$ – Probabilitytheoryapprentice Aug 25 '16 at 9:30
  • $\begingroup$ Here $f''(1)=0$ $\endgroup$ – iamvegan Aug 25 '16 at 9:33
  • $\begingroup$ Not that it is necessary here, but ... Have you covered Taylor series? Thinking in terms of Taylor series makes this easy. Let $t=x-1$. In terms of that variable you are looking at the function $f(t)=t/\sqrt{2-t}$ and its derivatives at $t=0$. If you can find the $2014$th derivative of $1/\sqrt{2-t}$ at $t=0$, then Taylor series manipulations do the rest. $\endgroup$ – Jyrki Lahtonen Aug 25 '16 at 9:49
  • $\begingroup$ @JyrkiLahtonen That could work well. Will try it as well later. $\endgroup$ – MathIsTheWayOfLife Aug 25 '16 at 9:56
5
$\begingroup$

Hint $$f(x)= \frac{x-1}{\sqrt{3-x}}=\frac{2}{\sqrt{3-x}}-\frac{3-x}{\sqrt{3-x}}=2(3-x)^{-\frac{1}{2}}-(3-x)^{\frac{1}{2}}$$

$\endgroup$
  • 1
    $\begingroup$ oh you already posted. I was goint to put same hint. cheers! $\endgroup$ – Max Payne Aug 25 '16 at 9:35
4
$\begingroup$

If one knows the following standard Taylor series expansion,

$$ \frac{1}{\sqrt{1-t}}=\sum_{n=0}^\infty \frac{{2n \choose n}}{2^{2n}}\:t^n, \quad |t|<1, \tag1 $$

then one gets $$ f(x)= \frac{x-1}{\sqrt{3-x}}=\frac1{\sqrt{2}}\cdot\frac{x-1}{\sqrt{1-\frac{x-1}2}}=\frac1{\sqrt{2}}\cdot\sum_{n=0}^\infty \frac{{2n \choose n}}{2^{3n}}\:(x-1)^{n+1} $$ giving

$$ \frac{f^{(2015)}(1)}{2015!}=\frac1{\sqrt{2}}\:\frac{{4028 \choose 2014}}{2^{6042}}. \tag2 $$

$\endgroup$
  • $\begingroup$ +1. Don't try to write down explicitly the whole answer (2). It's pretty long. $\endgroup$ – Felix Marin Aug 25 '16 at 21:39
1
$\begingroup$

Hint. Observe that $$ \frac{x-1}{\sqrt{3-x}}=-\sqrt{3-x}+\frac{2}{\sqrt{3-x}}. $$ Then, show inductively that, for $n\ge 2$ $$ \frac{d^n}{dx^n}\sqrt{3-x}=-\frac{(2n-3)!}{2^{2n-2}(n-2)!}(3-x)^{-\frac{2n-3}{2}} $$

$\endgroup$
1
$\begingroup$

Using Leibniz Formula for higher derivatives $$((x-1)\cdot (3-x)^{-1/2})^{(2015)}=\sum_{k=0}^{2015}{2015 \choose k}(x-1)^{(k)}((3-x)^{-1/2})^{(2015-k)}.$$ Clearly the only summand that survives are the ones with $k=0,1$ as for higher orders $(x-1)^{(l)}=0$. Moreover for $x=1$ the $k=0$ the term is also zero because $1-1=0$. So the only remaining term is $$f^{(2015)}(1)=((x-1)\cdot (3-x)^{-1/2})^{(2015)}\Big|_{x=1}={2015 \choose 1}(x-1)^{(1)}((3-x)^{-1/2})^{(2015-1)}\Big|_{x=1}\\ ={2015 \choose 1}(-1)^{2014}(3-x)^{-1/2-2014}4027!!/2^{2014}\Big|_{x=1}\\ =2015(-1)^{2014}4027!!2^{-(1/2+4028)}$$.

$\endgroup$
0
$\begingroup$

$$ f(x)=\frac{x-1}{\sqrt{3-x}} $$ set $t=x-1$: $$ f(t)=\frac{t}{\sqrt{2-t}}=\frac{1}{\sqrt{2}}t(1-t)^{-\frac{1}{2}} $$ now use the taylor series for $(1+t)^\alpha$ (find it here): $$ f(t)=\sum_{n=0}^{\infty}\binom{-\frac{1}{2}}{n}\frac{t^{n+1}}{\sqrt 2} $$ now change index from $n+1\to n$: $$ f(t)=\sum_{n=1}^{\infty}\binom{-\frac{1}{2}}{n-1}\frac{t^{n}}{\sqrt 2} $$ so by definition of Taylor series the coefficient in front of the k-th power is the k-th derivative divided by k!, hence: $$ f^{(k)}_{x=1}=\binom{-\frac{1}{2}}{k-1}\frac{k!}{\sqrt 2}=\frac{2\cdot k!}{2^k\sqrt 2}\prod_{j=1}^{k-1}\frac{1-2j}{j}=\frac{(-1)^{k+1}2k}{2^k\sqrt 2}\prod_{j=1}^{k-1}(2j-1) $$ FINAL RESULT using the definition of double factorial (find it here): $$ f^{(k)}_{x=1}=\frac{(-1)^{k+1} 2k}{2^k\sqrt 2}(2k-3)!! $$ $$ f^{(2015)}_{x=1}=\frac{4030(4027)!!}{2^{2015}\sqrt 2}\approx 1.03\times 10^{5783} $$ Remark: the derivative is calculated in 0 for t, this means that it is calculated in $x=1$, just as you wanted.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.